Sağlık hizmetlerinde yüksek performanslı iş sistemleri (yüpis) araştırmaları: sistematik derleme - Danayiyen, Aysun; Danayiyen, Aysun (Gümüşhane Üniversitesi, 2023)
Bu araştırmanın amacı, sağlık hizmeti sunan kurumlarda yapılmış yüksek performanslı iş sistemleri (YÜPİS) araştırmalarının, hasta, çalışan ve örgüt çıktıları açısından değerlendirilmesi ve kullanılmış YÜPİS ölçüm araçları ile boyutlarının tespit edilmesidir. Araştırma verilerinin toplaması, analiz edilmesi, yorumlaması ve bulguların sunulmasında PRISMA rehberi ile sistematik derleme yöntemi kullanılmıştır. Araştırma kapsamında belirlenen kriterlere uygun bulunan 38 yayın değerlendirilmiştir. Araştırma kapsamında incelenen çalışmaların %74’ünün 2011 yılı ve sonrasında yapıldığı belirlenmiştir. Coğrafi, ekonomik, kültürel ve sağlık sistemi bakımından farklı özelliklere sahip ülkelerde yapılan araştırmalarda YÜPİS genellikle tek boyut ve yönetici perspektifi ile ölçülmüştür. Sağlık hizmetlerinin yönetiminde YÜPİS teorisinin önemli etkileri olduğu fakat özellikle kamu sağlık kurumlarında yapılmış daha fazla araştırmaya ve sağlık sektörüne özgü çok boyutlu bir ölçeğe ihtiyaç duyulduğu tespit edilmiştir. Sağlık sektöründe YÜPİS araştırmalarının mevcut sonuçlarını inceleyen bu çalışma, önemli bulgulara ve katkılara odaklanarak, eksikliklere dikkat çekmekte ve gelecekte yapılacak araştırmalar için öneriler getirmektedir.

This research aims to evaluate the high-performance work systems (HPWS) studies conducted in healthcare institutions in terms of patient, employee, and organizational outputs and to determine the dimensions with HPWS tools used. Systematic review with the PRISMA guide was used to collect, analyze, interpret the research data and present the findings. 38 publications that comply with the specified criteria were evaluated within the scope of the research. The systematic compilation method with the PRISMA guide was used for the collection, analysis, interpretation of the research data and the cells of the sections. It has been observed that HPWS applications in healthcare services have increased regularly in various countries in recent years. It was determined that 74% of the studies examined within the scope of this research were conducted in 2011 and after. In studies conducted in countries with different geographical, economic, cultural, and health system characteristics, HPWS has generally been measured with one dimension and from a manager perspective. It has been determined that the HPWS theory has important effects in the management of health services, but more research and a multidimensional scale specific to the health sector are needed, especially in public health settings. This study, which examines the current results of HPWS research in the health sector, focuses on the important findings and contributions, highlights the shortcomings, and makes recommendations for future research.
High-performance work systems ın health care management: a systematic review
Keywords: Yüksek performanslı iş sistemleri (YÜPİS); Sağlık yönetimi; Sistematik derleme; Hasta güvenliği; Çalışan güvenliği; Hastane performansı; High-performance work systems (HPWS); Health management; Systematic review; Patient safety; Employee safety; Performance of Hospital